The Role of Magazines in the Tradition of Literary Discourse and Debate: A Review - Rizvi, Syed Tariq Hussain; Hussain, Tahir (sourcecoder, 2023)
The importance of dialogue in civilized societies is certain, which leads to new ideas. The tradition of inviting intellectuals to join together on the platform of discussion and dialogue on behalf of various movements and organizations of Urdu literature has been stable. These are the forums which played an important role in the promotion of different types of thoughts in Urdu literature. Urdu literary magazines also established a unique tradition of organizing such forums. Literary magazines provided an opportunity not only to well-known writers and poets but also to common readers to participate in literary discourse. In this paper, an attempt has been made to present a brief review of such literary forums in some magazines published from Sindh in order to highlight the role of literary magazines in the promotion of this tradition.